Global burden and trends of leukemia attributable to high body mass index risk in adults over the past 30 years - Xiao, Hang; Hu, Xiao; Li, Pengfei; Deng, Jianchuan (Frontiers in Oncology, 2024)
Background: High BMI (Body Mass Index) is a significant factor impacting health, with a clear link to an increased risk of leukemia. Research on this topic is limited. Understanding the epidemiological trends of leukemia attributable to high BMI risk is crucial for disease prevention and patient support.Methods: We obtained the data from the Global Burden of Disease Study, analyzing the ASR (age-standardized rates), including ASDR (age-standardized death rate) and age-standardized disability-adjusted life years (DALYs) rate, and estimated annual percentage change (EAPC) by gender, age, country, and region from 1990 to 2019.Results: In 2019, deaths and DALYs have significantly increased to 21.73 thousand and 584.09 thousand. The global age-standardized death and DALYs rates have slightly increased over the past 30 years (EAPCs: 0.34 and 0.29). Among four common leukemia subtypes, only CML (Chronic Myeloid Leukemia) exhibited a significant decrease in ASDR and age-standardized DALYs rate, with EAPC of -1.74 and -1.52. AML (Acute Myeloid Leukemia) showed the most pronounced upward trend in ASDR, with an EAPC of 1.34. These trends vary by gender, age, region, and national economic status. Older people have been at a significantly greater risk. Females globally have borne a higher burden. While males have shown an increasing trend. The regions experiencing the greatest growth in ASR were South Asia. The countries with the largest increases were Equatorial Guinea. However, It is worth noting that there may be variations among specific subtypes of leukemia. Regions with high Socio-demographic Index (SDI) have had the highest ASR, while lowmiddle SDI regions have shown the greatest increase in these rates. All ASRs values have been positively correlated with SDI, but there has been a turning point in medium to high SDI regions.Conclusions: Leukemia attributable to high BMI risk is gradually becoming a heavier burden globally. Different subtypes of leukemia have distinct temporal and regional patterns. This study's findings will provide information for analyzing the worldwide disease burden patterns and serve as a basis for disease prevention, developing suitable strategies for the modifiable risk factor.